The incubation period of hepatitis E genotype 1: insights from pooled analyses of travellers. Issue 12 (24th May 2018) - Azman, A. S.; Ciglenecki, I.; Oeser, C.; Said, B.; Tedder, R. S.; Ijaz, S.
Abstract: Hepatitis E virus genotype 1 (HEV G1) is an important cause of morbidity and mortality in Africa and Asia. HEV G1's natural history, including the incubation period, remains poorly understood, hindering surveillance efforts and effective control. Using individual-level data from 85 travel-related HEV G1 cases in England and Wales, we estimate the incubation period distribution using survival analysis methods, which allow for appropriate inference when only time ranges, rather than exact times are known for the exposure to HEV and symptom onset. We estimated a 29.8-day (95% confidence interval (CI) 24.1–36.0) median incubation period with 5% of people expected to develop symptoms within 14.3 days (95% CI 10.1–21.7) and 95% within 61.9 days (95% CI 47.4–74.4) of exposure. These estimates can help refine clinical case definitions and inform the design of disease burden and intervention studies.